Intellectuals, rights and the censorship of public diversions in the dictatorship: tensions, accommodations and ambivalences (1967-1985) - Maia, Tatyana de Amaral (Revista de História, 2021)
The aims of this article is to investigate the debate on public entertainment censorship produced by intellectuals acting inside the Ministry of Education and Culture between 1967 and 1985. Throughout the dictatorship, it is possible to observe three movements of the CFC around the theme: criticism to censorship until 1968; the project of cultural censorship, forwarded by Gilberto Freyre, in 1975; and the debate on censorship during the democratic transition. In these three moments, there was intense discussion about the legitimacy of censorship and what would be the positioning of a collegiate dedicate to culture in relation to the action of censorship. The performance of an ideologically heterogeneous group of right-wing intellectuals created constant tension inside the “Conselho” around the action of censorship becoming a factor of internal breakdown.